Fabrication of a highly sensitive electrochemiluminescence chlorpromazine sensor using a Ru(bpy)32+ incorporated carbon quantum dot–gelatin composite film. Issue 6 (1st February 2017) - Liu, Zhimin; Zhang, Fang; Cui, Lin; Wang, Kang; Zhan, Haijun
Abstract : A novel electrochemiluminescence sensing platform for the sensitive detection of chlorpromazine (CPZ) was fabricated based on a Ru(bpy)3 2+ /carbon quantum dots/gelatin composite film. Abstract : A novel electrochemiluminescence sensing platform for the sensitive detection of chlorpromazine (CPZ) was fabricated based on a Ru(bpy)3 2+ /carbon quantum dots/gelatin composite film. Carbon quantum dots (CQDs) in the composite film which have the ability to enhance the ECL intensity were synthesized by a simple and cost-saving method. As Ru(bpy)3 2+ was entrapped in the gelatin (Gel), the efficient immobilization of Ru(bpy)3 2+ could be achieved, which resulted in a stable ECL signal. In addition, the ECL signal on the Ru(bpy)3 2+ /CQDs/Gel composite modified electrode was greatly amplified by CPZ. The electrochemical and ECL behaviors of the proposed sensor were investigated. Under the optimum conditions, the ECL intensity was well-proportional to the logarithm of CPZ concentration in the range of 5.0 × 10 −10 to 1.0 × 10 −5 M, with the detection limit as low as 8.0 × 10 −11 M (S/N = 3). Furthermore, the ECL sensor was successfully applied for the determination of CPZ in spiked urine samples and exhibited a desirable result, which indicated that this sensor has potential application in CPZ analysis in real samples.